Management of pregnancy in women with monogenic diabetes due to mutations in GCK, HNF1A and HNF4A genes - Crowley, M. T.; Paponette, B.; Bacon, S.; Byrne, M. M. (Frontiers in Genetics, 2024)
Women with maturity-onset diabetes of the young (MODY) need tailored antenatal care and monitoring of their offspring. Each MODY subtype has different implications for glycaemic targets, treatment choices and neonatal management. Hyperglycaemia of MODY is often first diagnosed in adolescence or early adulthood and therefore is clinically relevant to pregnant women. MODY remains an under-recognised and undiagnosed condition. Pregnancy represents an opportune time to make a genetic diagnosis of MODY and provide precision treatment. This review describes the nuance of antenatal care in women with MODY and the implications for pregnancies affected by a positive paternal genotype. Mutations in hepatic nuclear factor 1-alpha (HNF1A) and 4-alpha (HNF4A) genes are associated with progressive β-cell dysfunction resulting in early onset diabetes. Patients are largely managed with sulphonylureas outside of pregnancy. Macrosomia and persistent neonatal hypoglycaemia are reported in 54% and 15% of HNF4A genotype positive offspring respectively with a median increase in birthweight of 790 g. Close observation of foetal growth in utero allows optimal timing of delivery to minimise peri- and postpartum materno-foetal complications. Glucokinase (GCK)-MODY causes mild fasting hyperglycaemia which does not require treatment outside of pregnancy. Birthweight of offspring of maternal carriers is dependent on foetal genotype; heterozygous mutation carriers are usually normal weight while genotype negative offspring are large for gestational age (600 g heavier). Affected offspring of paternal carriers may be small for gestational age (500 g lighter). Serial growth scans with measurement of the abdominal circumference indirectly differentiate foetal genotype. Measurement of cell free foetal DNA in maternal blood from the late first trimester is superior to traditionally used ultrasound to distinguish foetal genotype. Cost and accessibility may limit its use.